PHYLOGENETIC CHARACTERIZATION OF HIGHLY PATHOGENIC NEWCASTLE DISEASE VIRUS ISOLATED IN 2013 IN A PULTRY FARM OF SOUTHEASTERN KAAKHSTAN - Karamendin, K.O.; Kydyrmanov, A.I.; Asanova, S.E.; Seidalina, A.; Khan, E. Ja.; Daulbaeva, K.D.; Kasymbekov, E.T.; Suleimenova, S.A.; Zhumatov, K.H.; Sayatov , M.H. (Eurasian Journal of Applied Biotechnology, 2014)
In 2013in a poultry farm in South-Eastern Kazakhstan, an outbreak of acute infectious disease has occurred among 30-days-old domestic chickens. Positive results were obtained at screening of the collected materials in PCR and of specific bands of 132 bp were detected, indicating the presence of Newcastle disease virus RNA in samples. After isolation of the virus in embryonatedchicken embryos, its subsequent purification, concentration and RNA extraction, sequencing of the gene encoding the fusion protein (F- protein) was performed.. In the result of sequencing, the nucleotide sequence of 999 bp was decoded, which includes the cleavage site of the fusion protein that is important to identify its pathogenicity. The results of phylogenetic analysis of Newcastle disease virus strain isolated from sick chickens are shown on the basis of sequencing of the F- gene. It is shown that on the fusion protein gene, all the studied viruses classified in two phylogenetically distinct classes - 1 and 2. Kazakhstan APMV-1/chicken/Almaty/41/2013 strain was in a group of viruses belonging to genotype VII in Class 2. This group is formed by the APMV -1 viruses, containing polybasic amino acids KRQKR in the sequence of the fusion protein, that indicates their high pathogenicity to birds. Territory of circulation of this highly pathogenic genotype virus covers vast territory on the Asian subcontinent spaces, affecting a significant number of avian fauna. Supposition of an exogenous origin of the virus was proposed, as poultry in this farm wasimmunized with a vaccine containing lentogenic (avirulent) Newcastle disease virus strain La Sota. It is known that the use of a vaccine containing any genotype of Newcastle disease virus protects poultry against mortality and clinical signs of disease, but the virus release into environmentwas not stopped, that may contribute to the continuous spread of infection especially in cases where the introduced virus has divergence in the genetic structurewith vaccine strain.